2009
DOI: 10.1111/j.1474-919x.2009.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐breeding diet influences ornament size in the Rhinoceros Auklet Cerorhinca monocerata

Abstract: Understanding the mechanisms that influence variation in sexually selected ornaments in seabirds has been challenging owing to the difficulty of capturing and sampling individuals outside of the breeding period when ornaments are usually grown. Stable carbon (d 13 C) and nitrogen (d 15 N) isotopes were used to examine the influence of pre-breeding diet composition on ornament size in the Rhinoceros Auklet Cerorhinca monocerata, a socially monogamous seabird that breeds in the North Pacific. We analysed stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
1
15
1
Order By: Relevance
“…Contrary to results from other regions that euphausiids are an important prebreeding diet item for adult rhinoceros auklets (Hobson et al 1994, Davies et al 2009, Ito et al 2009, Sorensen et al 2010, our mixing models indicated that euphausiids were not an important component of adult diet during any period sampled (mean < 5% for all periods; Table 2). Rhinoceros auklets at ANI may not have fed as heavily on euphausiids as in other regions, but it is also possible that the isotope values of the breast feathers did not accurately reflect diet during the pre-breeding period.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to results from other regions that euphausiids are an important prebreeding diet item for adult rhinoceros auklets (Hobson et al 1994, Davies et al 2009, Ito et al 2009, Sorensen et al 2010, our mixing models indicated that euphausiids were not an important component of adult diet during any period sampled (mean < 5% for all periods; Table 2). Rhinoceros auklets at ANI may not have fed as heavily on euphausiids as in other regions, but it is also possible that the isotope values of the breast feathers did not accurately reflect diet during the pre-breeding period.…”
Section: Discussioncontrasting
confidence: 99%
“…Parents carry whole fishes and cephalopods in their bills and deliver them to chicks in "bill-loads" (Thayer and Sydeman 2007), with each adult averaging one bill-load delivered a night (Takahashi et al 1999). Adults consume krill in the spring pre-breeding and incubation periods in some regions (Ito et al 2009, Sorensen et al 2010. Adult trophic level increases after chicks hatch, likely because adults switch at this time to eating fish with greater caloric content, which are required by growing chicks (Ito et al 2009, Davies et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…While such perturbations are known to influence breeding performance (Gaston et al 2005, Barbraud & Weimerskirch 2006, Hipfner 2008, their influence on seabirds during the nonbreeding period is more difficult to ascertain due to incomplete knowledge of distributions, particularly of pelagic species in winter. Winter conditions have carry-over effects on breeding performance (Harris & Wanless 1996, Sorensen et al 2009, Smith & Gaston 2012, and can strongly influence both adult survival and rates of recruitment to breeding populations (Harris & Wanless 1996, Wilson et al 2001, Frederiksen et al 2008, Ballerini et al 2009, Jenouvrier et al 2009. The impact of spatially explicit habitat perturbations on the wintering grounds depends on the extent to which species and breeding populations converge (Esler 2000, Webster et al 2002, Phillips et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Revealing such seasonal interactions Runge and Marra 2005) is critical to understanding the ecology of migratory birds. However, no study to date has examined how stationary nonbreeding (hereafter: winter) habitat effects on spectral signal production may carry over to influence breeding success (but see Saino et al 2004;Sorensen et al 2010 for studies of ornament size).…”
Section: Introductionmentioning
confidence: 99%